The Effect of Principal Leadership on Student Bullying Behavior in Public Senior High Schools in Manado City - Rinna Y. Kasenda; Joulanda A. M. Rawis; Harol R. Lumapow; Tellma M. Tiwa (International Journal of Education, Information Technology, and Others, 2026)
Bullying in senior high school settings constitutes a serious issue in educational management, as it directly affects students’ sense of safety, psychological well-being, and the overall quality of the learning process. Principals are normatively positioned as strategic actors in fostering a safe, violence-free school culture. However, the assumption that principal leadership automatically exerts a direct impact on students’ bullying behavior has rarely been examined empirically, particularly within the context of public schools. This study aims to critically analyze the influence of principal leadership on bullying behavior among students in public senior high schools in Manado City. This study employed a quantitative approach using an explanatory survey design. The research population consisted of all students enrolled in public senior high schools in Manado City, with a sample of 385 students determined using the Lemeshow formula. Data were collected through Likert-scale questionnaires measuring principal leadership and students’ bullying behavior. The data were analyzed using Structural Equation Modeling (SEM) with AMOS software, including validity testing, reliability testing, model fit evaluation, and structural relationship analysis. The results indicate that principal leadership does not have a direct and significant effect on student’s bullying behavior. This finding suggests that principal leadership operates indirectly and primarily functions at the structural and policy levels, whereas bullying behavior is shaped through students’ everyday social dynamics. Therefore, bullying prevention cannot rely solely on formal leadership, but requires the strengthening of school systems, a supportive school climate, and consistent educational practices. This study contributes theoretically by affirming that the relationship between principal leadership and bullying behavior is non-linear. Practically, the findings recommend that principals should not focus exclusively on administrative aspects, but also enhance the implementation mechanisms of anti-bullying policies to effectively reach students’ actual behavior within the school environment.